Research Trend in Halal: A Bibliometric Analysis Using the Scopus Database - Siti Nurunnajwa Shamsudin; Elistina Abu Bakar; Syuhaily Osman; Nuradli Ridzwan Shah Mohd Dali; NusaibahAnuar Musaddad (HH Publisher, 2024)
Journal of Halal Industry and Services Volume: 5 No: 1 (page: 1-21)